PEMANFAATAAN LIMBAH AIR KELAPA SEBAGAI POC PADA KWT MENTARI KECAMATAN PONTIANAK TENGGARA - Sutikarini Sutikarini; Agusalim Masulili; Agus Suyanto (Jurnal Abdimas Bina Bangsa, 2023)
Partner activities in community service are planned as many as 1 group, namely the Mentari women farmer group. The observation results show that the cultivation of horticultural crops has been carried out conventionally. There is a potential waste that has not been utilized, namely coconut water. Research on the application of coconut water POC has been widely applied and applied to the community. It’s necessary to conduct outreach to activity partners in the manufacture and application of coconut water POC. The method used in this Community Partnership Program (PKM) scheme is the extension method. This method involves counseling about the substance of the activity of making liquid organic fertilizer from coconut water waste, accompanied by demonstrations in its realization. This activity starts from the preparation stage, the implementation stage and counseling as well as the evaluation stage. The results of this PKM, the partner group has increased both affective (knowledge) from knowing about POC Coconut Water by 15% to 80%, cognitive (attitude) where partners are interested in trying to apply and skills where partners can make POC Coconut Water and apply it to garden plants